2016
DOI: 10.21685/1680-0826-2016-10-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Metchnikovella Dogieli Sp. N. (Microsporidia: Metchnikovellida), a Parasite of Archigregarines Selenidium Sp. From Polychaetes Pygospio Elegans

Abstract: SummaryCysts and free spores of a metchnikovellid microsporidium were found in several specimens of an archigregarine Selenidium sp. isolated from polychaetes Pygospio elegans. Samples were collected at the littoral area of the Kandalaksha Bay of the White Sea in the year 2016. We examined this material with high-quality light optics in stained and live preparations. The structure of cysts and the host range suggest that this species belongs to the genus Metchnikovella Caullery et Mesnil, 1897. The length of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…The host name and the infection caused by microsporidia Metchnikovella incurvata and M. oviformis are available evidence from this species ( Caullery & Mesnil, 1914a ; Caullery & Mesnil, 1914b ; Caullery & Mesnil, 1919 ). We believe that we collected namely eugregarines P. pygospionis in the White Sea because they parasitized P. elegans polychaetes and were found to be infected by the microsporidium M. incurvata ( Paskerova et al, 2016 ; Rotari, Paskerova & Sokolova, 2015 ; Sokolova et al, 2013 )—in these articles, this gregarine is called Polyrhabdina sp.). Our transmission electron microscopic study of this eugregarine revealed peculiarities of the pellicle structure: the presence of loops of the internal lamina under epicytic grooves, which is not typical for eugregarines, and the absence of the internal lamina links at the epicytic crest bases, which is characteristic of some aseptate and septate eugregarines, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host name and the infection caused by microsporidia Metchnikovella incurvata and M. oviformis are available evidence from this species ( Caullery & Mesnil, 1914a ; Caullery & Mesnil, 1914b ; Caullery & Mesnil, 1919 ). We believe that we collected namely eugregarines P. pygospionis in the White Sea because they parasitized P. elegans polychaetes and were found to be infected by the microsporidium M. incurvata ( Paskerova et al, 2016 ; Rotari, Paskerova & Sokolova, 2015 ; Sokolova et al, 2013 )—in these articles, this gregarine is called Polyrhabdina sp.). Our transmission electron microscopic study of this eugregarine revealed peculiarities of the pellicle structure: the presence of loops of the internal lamina under epicytic grooves, which is not typical for eugregarines, and the absence of the internal lamina links at the epicytic crest bases, which is characteristic of some aseptate and septate eugregarines, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations suggest that in co-infection of P. pygospionis and S. pygospionis in Pygospio elegans ( Paskerova et al, 2018 ; this study) each parasite species is more abundant than in monoinfections. Eugregarines, blastogregarines, and archigregarines regularly harbour metchnikovellid microsporidia ( Caullery & Mesnil, 1897a ; Caullery & Mesnil, 1897b ; Caullery & Mesnil, 1919 ; Ganapati, 1946 ; Mackinnon & Ray, 1931 ; Mikhailov et al, 2021 ; Paskerova et al, 2016 ; Paskerova et al, 2018 ; Rotari, Paskerova & Sokolova, 2015 ; Sokolova et al, 2013 ; Sokolova et al, 2014 ; Table S3 ). Further studies focused on metchnikovellids that infect gregarines co-occurring in the same spionid polychaete may shed some light on the diversification of metchnikovellids and co-evolution of gregarine hosts and their hyperparasitic microsporidia.…”
Section: Discussionmentioning
confidence: 99%
“…Metchnikovella dogieli, the second parasite of S. pygospionis, has oval, sometimes slightly bent spore sacs with one polar plug (Figure 2, G). Spore sacs are significantly larger than those of M. dobrovolskiji, measuring 9.5 -34 µ m in length and 4.8 -9.2 µ m in width [31]. The number of spores per sac varies from 7 to 18 (on average 12).…”
Section: Four Hyperparasites For One Super-host: Metchnikovellids Inh...mentioning
confidence: 96%
“…Polyrhabdina pygospionis is a host for Metchnikovella spiralis (Figure 2, C) and M. incurvata (Figure 2, D, E), while Selenidium pygospionis can harbor M. dobrovolskiji (Figure 2, F, G), and M. dogieli (Figure 2, H). We have monitored this system in the White Sea for over a decade [11][12][29][30][31][32][33][34]. In recent years, screenings have also been initiated in the Barents Sea.…”
Section: What Are Metchnikovellids?mentioning
confidence: 99%
See 1 more Smart Citation